2009
DOI: 10.1186/1477-7827-7-143
|View full text |Cite
|
Sign up to set email alerts
|

Potential biological role of poly (ADP-ribose) polymerase (PARP) in male gametes

Abstract: Maintaining the integrity of sperm DNA is vital to reproduction and male fertility. Sperm contain a number of molecules and pathways for the repair of base excision, base mismatches and DNA strand breaks. The presence of Poly (ADP-ribose) polymerase (PARP), a DNA repair enzyme, and its homologues has recently been shown in male germ cells, specifically during stage VII of spermatogenesis. High PARP expression has been reported in mature spermatozoa and in proven fertile men. Whenever there are strand breaks in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
89
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(93 citation statements)
references
References 219 publications
(291 reference statements)
4
89
0
Order By: Relevance
“…The association between sDF and apoptosis also was investigated by using another apoptotic marker, the cleaved form of PARP (cPARP), (12,47). Figure 5A reports a typical dot plot showing the immunofluorescent detection of cPARP in TUNEL-labeled sperm.…”
Section: E C H a N I S M S O F S P E R M D N A F R A G M E N T A T I Omentioning
confidence: 99%
“…The association between sDF and apoptosis also was investigated by using another apoptotic marker, the cleaved form of PARP (cPARP), (12,47). Figure 5A reports a typical dot plot showing the immunofluorescent detection of cPARP in TUNEL-labeled sperm.…”
Section: E C H a N I S M S O F S P E R M D N A F R A G M E N T A T I Omentioning
confidence: 99%
“…It possesses antiproliferative, anticarcinogenic and chemopreventive potential (1,2). The antitumor efficacy of curcumin has been documented in animal models as well as in phase I clinical trials with multiple cancer types (3)(4)(5)(6)(7). The molecular targets and therapeutics of curcumin in health and disease have been studied before (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…The antitumor efficacy of curcumin has been documented in animal models as well as in phase I clinical trials with multiple cancer types (3)(4)(5)(6)(7). The molecular targets and therapeutics of curcumin in health and disease have been studied before (5)(6)(7). These studies have reported that curcumin had biological and medicinal properties as well as anticancer potential in preclinical and clinical studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As we know, one of the most important functions of PARP is to help repair single-stranded DNA nicks, and the cleaved-PARP is critically involved in the intrinsic apoptosis pathway and considered to be a marker of apoptosis. 35,36 In the present study, we observed the expression of proapoptotic and antiapoptotic members of the Bcl-2 family, which is the mitochondrial-related death switch. The members of Bcl-2 homology are divided into three main groups based on function and regions of the domains: multi-domain antiapoptotic proteins (Bcl-2, Bcl-xL, Bcl-w, Mcl-1, and A1), multi-domain proapoptotic proteins (Bax and Bak), and BH3-only proapoptotic proteins (Bid, PUMA, Bim, and NOXA), trigger the activation of Bak and Bax.…”
mentioning
confidence: 72%